Determinan Akuntabilitas Kinerja Instansi Pemerintah - Putri, Anandita; Budi Partiningsih, Diah; Fachrunnisa, Zidni Husnia; Adyaksana, Rahandhika Ivan (Akmenika: Jurnal Akuntansi dan Manajemen, 2025)
This research was carried out to examine the factors that influence the accountability of government agency performance. Accountability for the performance of government agencies is the obligation of every government agency to account for its performance to the public. This accountability includes the results achieved, processes and resources used. Factors in implementing performance-based budgeting, human resource competence and religiosity together can create a government that is better, cleaner and more accountable to the public. The research subject is the Regional Apparatus Unit in Gunungkidul Regency. There are 19 institutions and agencies that received an "A" rating in the 2022 Government Institution Performance Accountability Report, with a total of 114 samples selected using objective sampling techniques. Information is collected via questionnaires. The analysis shows that the implementation of performance-based budgeting and HR capabilities have a significant impact on the accountability of government agency performance, while religion has no influence. The results of the study concluded that increasing the implementation of performance-based budgeting and human resource capabilities can increase the accountability of the performance of government institutions, while the level of religiosity does not have a significant impact.